Factors affecting the successful implementation of customer relationship management in 3-to-5-star hotels in Viet Nam - Nguyen Viet Thai; Bui Thi Quynh Trang; Nguyen Le Dinh Quy; Nguyen Thi Quynh Huong; Vu Thi Thu Huyen (Cogent Social Sciences)
The study aims to assess the factors affecting the successful implementation of customer relationship management (CRM), as well as the relationship between the successful implementation of CRM and customer loyalty, in 3-to-5-star hotels in Vietnam. The study carried out integrating 3 theories RBV, RM and CM to identify the main components of CRM: human resources, technology and processes. On that basis, the article has identified 6 factors affecting successful CRM implementation in relation to the main components of CRM including: senior leaders’ commitments, CRM strategies, business procedures, hotel culture, technology infrastructure and database. By survey with a total sample size of 396 questionnaires. The participants included executive managers, vice directors, head of departments and head of divisions 3–5 star hotels in Hanoi, Ho Chi Minh City and Da Nang – 3 tourist cities of Vietnam in the list of 10 best cities in Southeast Asia. They were directly engaged in the management and execution of hotel operations, including CRM implementation. Upon being filtered, the data was analyzed by a Cronbach’s Alpha coefficient, regression analysis, and hypothesis testing to measure the impact level of the factors affecting the successful implementation of CRM, and the relationship between the successful implementation of CRM and customer loyalty. The findings obtained indicate that all 6 factors have a positive impact on the successful implementation of CRM, and the successful implementation of CRM has a positive and significant impact on customer loyalty. Additionally, theoretical and practical implications were proposed to help managers of 3-to-5-star hotels in Vietnam gain a better understanding of the importance of resources, so as to make the best preparations before implementing CRM and building customer loyalty. Further research orientations were also presented.